Aplicação de Ressonância Nuclear Magnética -¹H RMN no diagnósticode hiperglicemia gestacional - Schiavenin, Ariane (My University, 2025)
NMR (Nuclear Magnetic Resonance) has been used as a tool for diagnosing diseases, via metabolomic analysis, with success in recent times. It is an analysis that evaluates the profile of compounds released/excreted in different matrices, such as blood, plasma, urine, among others. Dysglycemia is the most common metabolic disorder during pregnancy. lt is estimated that approximately 16% of live births are from women who had some form of hyperglycemia during pregnancy. However, it is a difficult process to diagnose. Therefore, the main objective of this study was to understand the application of NMR for the early diagnosis of gestational diabetes (GDM). As a result, this work generated a literature review -The potential of 1 H NMR spectroscopy for diabetes diagnosis: a review of current applications and future directions, which was recently submitted to the journal Diabetes research and clinicai practice (https:/ /www .sciencedirect.com/journal/diabetes-research-and-clinical-practice ), which illustrates advances in the application ofthis technique for diagnosis diabetes. Furthermore, as the main product of this thesis, 80 urine samples were collected and evaluated from pregnant women in four different groups to understand the application ofNMR for diagnosis of GDM. ln order to that happen, we had the partnership of the High Risk Outpatient Clinic of the General Hospital of the University of Caxias do Sul. These samples were analyzed by Ultra High Performance Liquid Chromatography with High Resolution Mass Detection (ULCMS) in the United Kingdom, in partnership with Professor RuAngelie Edrada-Ebel, at Strathclyde University in Glasgow - SCO. The results generated data for the second article entitled - 1HNuclear Magnetic Resonance analysis of urine as a diagnostic tool for gestational hyperglycemia - which is being prepared for subsequent publication. Thus, based on this issue, in order to better understand gestational hyperglycemia, its traditional form of diagnosis and the role of new analytical technologies in elucidating the diagnosis, a complete literature review was initially carried out in order to understand the role of hyperglycemia and metabolomics. As complementary manner, in order to better understand the role ofNMR and its applications, this thesis also presents a study with applications of the technique as a tool to quantify caffeine in thermogenic capsules for quality control ofpre-workout agents entitled -Too much or too little caffeine? determination of content in thermogenic capsules by quantitative IH Nuclear Magnetic Resonance ( qNMR)., which was published in the Journal of Pharmaceutical and Biomedical Analysis in 2025 (doí: https://doi.org/10.1016/j.jpba.2025.116832). Thus, it is a thesis that demonstrates the various possibilities of application of NMR, with a main focus on demonstrating its application for metabolomic evaluations, such as in the diagnosis of diabetes, as well as for direct quantification of active ingredients, as in the case of caffeine for quality control. [resumo fornecido pelo autor]
A RNM (Ressonância Magnética Nuclear), tem sido utilizada como ferramenta para diagnóstico de doenças, via análise metabolomica, com êxito nos últimos tempos. Se trata de uma análise que avalia o perfil dos compostos liberados/excretados em diferentes matrizes, como sangue, plasma, urina entre outros. A disglicemia é o distúrbio metabólico mais comum durante a gravidez. São estimados que aproximadamente 16% dos nascidos vivos são de mulheres que tiveram alguma forma de hiperglicemia durante a gravidez. No entanto, se trata de um processo de dificil diagnóstico. Assim, o principal objetivo deste trabalho foi compreender a aplicação da RMN para diagnostico precoce de diabetes gestacional (DMG). Como resultados, este trabalho gerou uma revisão de literatura - The potential of 1 H NMR specroscopy for diabetes diagnosis: a review of current applications and future directions, a qual foi recentemente submetida a revista Diabetes research and clinicai practice (https:/ /www .sciencedirect.com/joumal/diabetes-research-and-clinical-practice ), que ilustra os avanços da aplicação desta técnica para diagnostico exclusivo de diabetes. Ainda, como produto principal desta tese, foram coletadas e avaliadas 80 amostras de urinas de gestantes em quatro grupos diferentes para compreender a aplicação da RMN para diagnostico de DMG. Para isso, tivemos a parceria do ambulatório de Alto Risco do Hospital Geral da Universidade de Caxias do Sul. Estas mesmas amostras foram analisadas por Cromatografia a Líquido de Ultra Eficiência com detector de Massas de Alta Resolução (CLUE-MS) no Reino Unido, em parceria com a professora RuAngelie Edrada-Ebel, na Strathclyde University em Glasgow - SCO. Os resultados geraram dados para o segundo artigo intitulado - 1 H- Nuclear Magnetic Resonance analysis of urine as diagnostic too/ for gestational hyperglycemia - que está sendo preparado para publicação subsequente. Assim, a partir desta problemática, afim de compreender melhor a hiperglicemia gestacional, sua forma tradicional de diagnóstico e o papel de novas tecnologias analíticas na elucidação do diagnóstico, inicialmente procedeu-se com uma revisão de literatura completa com a finalidade de compreender o papel da hiperglicemia e análise metabolômica. De forma complementar, com a finalidade de compreender ainda mais o papel da RMN e suas aplicações, esta tese também traz um estudo com aplicações da técnica para quantificar cafeína em capsulas termogênicas para controle de qualidade de agentes pré-treinos intitulado - Too much or too little caffeine - determination of content in thermogenic capsules by quantitative 1 H Nuclear Magnetic Resonance (qNMR), o qual foi publicada na Journal of Pharmaceutical and Biomedical Analysis em 2025 (doí: https://doi.org/10.1016/j.jpba.2025.116832). Assim, é uma tese que tem demonstra as várias possibilidades de aplicação da RMN, com foco principal em demostrar a aplicação da mesma para avaliações metabolomicas, como no diagnostico de diabetes, bem como para quantificação direta de princípios ativos, como no caso da cafeína para controle de qualidade. [resumo fornecido pelo autor]
Keywords: Hiperglicemia - Diagnóstico; Ressonância magnética nuclear; Diabetes na gravidez; Doenças - Diagnóstico; Metabólitos; Hyperglycemia - Diagnosis; Nuclear magnetic resonance; Diabetes in pregnancy; Diseases - Diseases; Metabolites